Anatomical Study of Axillary Artery Variation. - Farhan, Thaer M.; Selman, Mohammad O. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The axillary artery is a direct continuation of the subclavian artery. The axillary artery is usually described as giving off six branches. The first part gives superior thoracic artery. The second part gives lateral thoracic (LT) and thoracoacromial(TAC) arteries. The third part gives three, subscapular(SS), anterior circumflex humeral(ACH)and posterior circumflex humeral(PCH) arteries. Anatomical variations in the branching pattern of axillary artery are quiet common and typically include the subscapular artery(SS), lateral thoracic artery(LT) and the posterior circumflex humeral artery(PCH). The variation of the axillary artery branching pattern has anatomical as well as clinical and surgical relevance given the proximity to the shoulder joint and humerus.Patients & Method: Bilateral axilla dissection was conducted on 26 embalmed axillae (13 cadavers) to allow examination of the axillary artery and its branches. The study was carried out in Department of Human Anatomy, College of Medicine.Results: The classical branching pattern of the LT originating from the axillary artery posterior to the pectoralis minor muscle and the SS producing the circumflex scapular (CS) artery and thoracodorsal(TD) occurred in 77%. The SS was observed originating from the LT 7% of the time. The LT was observed originating from the SS 5% of the time. The LT was observed producing the circumflex scapular artery and TD in the absence of SS 2.5% of the time. The PCH originated from four different sources, from the third part of axillary artery as is classically described in 77%. From the SS 11%. From deep brachial artery DB 9% and from LT 2%.Conclusion: Vascular variation in the axillary artery and its branches is quiet common , This variation should be considered seriously as will implicate risk of bleeding during surgery in the axilla and also the difficulty in interpretation of the angiography after axillary catheterization.